Environment and Mental's Health in The Pandemic Time Covid-19 in IGD Nurse Royal Prima Medan Hospital - Khainir Akbar; Sri Lestari Ramadhani Nasution; Ermi Girsang (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
The mental health of health workers during the COVID-19 pandemic period is a present issue that must be given more attention. It is because health workers are the spearhead of handling the COVID19 case, which is daily increasing. The purpose of the research to examine the mental health of IGD nurses at Royal Prima Hospital Medan by using variable demographic characteristics (age, gender, years of service), family environment, social environment, and work environment. This type of research is a quantitative study, with the research sample being all emergency room nurses at Royal Prima Hospital Medan. The data were processed using correlation analysis in SPSS. The results showed that the demographic characteristics, family environment, social environment, and work environment were positively correlated with mental health in IGD nurses at Royal Prima Medan Hospital. Suggestions for further research are to use a larger sample and be able to use other variables according to the theory of Cooper and Davidson